Politik Hukum Islam di Indonesia dan Malaysia: Suatu Kajian Perbandingan - Muin, Fatkhul (Al-Manahij: Jurnal Kajian Hukum Islam, 2017)
This study analyzes the viewpoint of Islamic law as a part of national law, where the part of society that cannot be separated from the Muslim majority state. Indonesia and Malaysia are two countries with Muslim majority population and are considered to have a same clump of lineage, but on the other aspects that influence the laws in the two countries they have differences, in which Indonesia is affected by the legal system of the Civil Law, while Malaysia is influenced by the legal system of Common Law. Such differences would affect the legal systems of both countries, not only in that aspect, but also will affect the Islamic laws in the countries which are predominantly. Muslim. In Indonesia, the existence of Islamic law can enter through Pancasila and Article 29 paragraph 1 and 2 of the Indonesian Constitution, while in Malaysia the existence of Islamic law can enter through the state recognition of the official religion of Malaysia that is Islam, according to article 3 paragraph 1 of the Constitution of Malaysia.